Accelerated Biodegradation of the Agrochemical Ametoctradin by Soil-Derived Microbial Consortia - Whittington, Hunter D.; Singh, Mahatam; Ta, Chanh; Azcárate-Peril, M. Andrea; Bruno-Bárcena, José M. (Frontiers in Microbiology, 2020)
Pesticide-resistant plant pathogens are an increasing threat to the global food supply and have generated a need for novel, efficacious agrochemicals. The current regulatory process for approving new agrochemicals is a tedious but necessary process. One way to accelerate the safety evaluation process is to utilize in vitro systems to demonstrate pesticide degradation by soil microbes prior to ex vivo soil evaluations. This approach may have the capability to generate metabolic profiles free of inhibitory substances, such as humic acids, commonly present in ex vivo soil systems. In this study, we used a packed-bed microbial bioreactor to assess the role of the natural soil microbial community during biodegradation of the triazolopyrimidine fungicide, ametoctradin. Metabolite profiles produced during in vitro ametoctradin degradation were similar to the metabolite profiles obtained during environmental fate studies and demonstrated the degradation of 81% of the parent compound in 72 hours compared to a half-life of 2 weeks when ametoctradin was left in the soil. The microbial communities of four different soil locations and the bioreactor microbiome were compared using high throughput sequencing. It was found that biodegradation of ametoctradin in both ex vivo soils and in vitro in the bioreactor correlated with an increase in the relative abundance of Burkholderiales, well characterized microbial degraders of xenobiotic compounds.